New Insights Into Cranial Synchondrosis Development: A Mini Review - Funato, Noriko (Frontiers in Cell and Developmental Biology, 2020)
The synchondroses formed via endochondral ossification in the cranial base are an important growth center for the neurocranium. Abnormalities in the synchondroses affect cranial base elongation and the development of adjacent regions, including the craniofacial bones. In the central region of the cranial base, there are two synchondroses present—the intersphenoid synchondrosis and the spheno-occipital synchondrosis. These synchondroses consist of mirror image bipolar growth plates. The cross-talk of several signaling pathways, including the parathyroid hormone-like hormone (PTHLH)/parathyroid hormone-related protein (PTHrP), Indian hedgehog (Ihh), Wnt/β-catenin, and fibroblast growth factor (FGF) pathways, as well as regulation by cilium assembly and the transcription factors encoded by the RUNX2, SIX1, SIX2, SIX4, and TBX1 genes, play critical roles in synchondrosis development. Deletions or activation of these gene products in mice causes the abnormal ossification of cranial synchondrosis and skeletal elements. Gene disruption leads to both similar and markedly different abnormalities in the development of intersphenoid synchondrosis and spheno-occipital synchondrosis, as well as in the phenotypes of synchondroses and skeletal bones. This paper reviews the development of cranial synchondroses, along with its regulation by the signaling pathways and transcription factors, highlighting the differences between intersphenoid synchondrosis and spheno-occipital synchondrosis.